Effect of moderate disorder on the absorbance of plasma spheres distributed in a host dielectric medium - V. Yannopapas; A. Modinos; N. Stefanou (NATO ASI "Photonic Crystals and Light Localization in the 21st Century, 2001)
Using a coherent-potential approximation, in conjunction with the on-shell method we developed for the study of photonic crystals, we study the effect of moderate disorder on light absorption by composite materials consisting of plasma spheres embedded in a host dielectric medium. We analyze our results by reference to the properties of a single sphere and to those of an infinite crystal. We find, in particular, that the absorption of light by a thin slab (a two-dimensional array of plasma spheres) is affected more strongly by disorder, in comparison to the absorbance of thick slabs consisting of many layers of spheres.